A2_3 A Nice Flight... TO HELL!!! - Filip, Tomasz; McMullan, Mac; Perks, Megan; Stylianou, Natalia (Physics Special Topics, 2021)
In this paper we look into the effects of drag on paper aeroplanes, specifically how much it heats it up. This could potentially be an issue if you make an aircraft out of a flammable material such as paper. By using a purely theoretical approach, we found that to set a paper aeroplane on fire just from the effect of drag it would have to be thrown at a velocity of 5725 ms^-1.